(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The security and confidentiality of computerized accounting information systems are crucial aspects in modern computerized accounting operations. Internal auditing plays a significant role in ensuring and protecting the security and confidentiality of these systems. This research aims to investigate the role of internal auditing in dealing with the security and confidentiality of computerized accounting information systems and its challenges. The study systematically examines the role of internal auditing in assessing and analyzing computerized accounting information systems to ensure the presence of strong and effective security controls. The role of internal auditing also includes verifying the implementation of security policies and procedures. The study found that internal auditing influences the effectiveness of computerized accounting information systems in municipal entities by ensuring the availability of accurate and complete information. It also facilitates the preparation of periodic reports on business operations, protects public funds, and provides recommendations to enhance security and confidentiality. However, internal auditing faces multiple challenges in ensuring the security and confidentiality of computerized accounting information systems.